Modeling neuron–glia interactions with the Brian 2 simulator - Stimberg,M; Goodman,DFM; Brette,R; De,Pittà M (2017)
Abstract Despite compelling evidence that glial cells could crucially regulate neural network activity, the vast majority of available neural simulators ignores the possible contribution of glia to neuronal physiology. Here, we show how to model glial physiology and neuron-glia interactions in the Brian 2 simulator. Brian 2 offers facilities to explicitly describe any model in mathematical terms with limited and simple simulator-specific syntax, automatically generating high-performance code from the user-provided descriptions. The flexibility of this approach allows us to model not only networks of neurons, but also individual glial cells, electrical coupling of glial cells, and the interaction between glial cells and synapses. We therefore conclude that Brian 2 provides an ideal platform to efficiently simulate glial physiology, and specifically, the influence of astrocytes on neural activity.